2018
DOI: 10.1186/s12871-018-0562-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different doses of dexmedetomidine as a rapid bolus for children: a double-blind, prospective, randomized study

Abstract: BackgroundDexmedetomidine (DEX), a highly sensitive α2-adrenoceptor agonist that possesses anxiolytic, sedative, and analgesic effects, has been documented as a preventative and treatment for emergence agitation (EA). The therapeutic should be given as a loading dose that is infused during a 10 min period, but if a rapid bolus injection is deemed to be hemodynamically appropriate, it would be a more opportune route of administration. So we studied the efficacy of different doses of DEX as a rapid bolus for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…In our included studies, DEX showed its effect in decreasing EA from the lowest dose of 0.15 μg/kg (26) to the highest dose of 1.86 μg/kg (41). Nine studies directly compared the effects of different doses of DEX on EA in children (22,30,33,43,44,56,75,76,79). The meta-regression analysis for these nine studies showed a statistically significant association between EA incidence and DEX dose (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our included studies, DEX showed its effect in decreasing EA from the lowest dose of 0.15 μg/kg (26) to the highest dose of 1.86 μg/kg (41). Nine studies directly compared the effects of different doses of DEX on EA in children (22,30,33,43,44,56,75,76,79). The meta-regression analysis for these nine studies showed a statistically significant association between EA incidence and DEX dose (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies reported the incidence of EA according to the different dose of DEX compared to placebo (22,30,33,43,44,56,75,76,79). We conducted a metaregression analysis to show the relationship between the dose of DEX and EA incidence, which revealed statistically significant evidence for an association between the log risk ratio for EA and the dose of DEX (P=0.013) (Figure 11).…”
Section: Relationship Between the Dose Of Dex And Incidence Of Eamentioning
confidence: 99%
“…Dexmedetomidine, as a highly selective α 2 adrenergic receptor agonist, can produce pharmacological effects of anti-anxiety, sedation, and analgesia without overt respiratory and circulatory inhibition in a routine dose ( 94 , 95 ). Meanwhile, dexmedetomidine can improve the cognitive function in children during recovery from general anesthesia ( 96 ) and contributes to dose-dependent inhibition of EA or ED after medical procedures ( 97 ). The optimal dose (ED 95 ) of dexmedetomidine for preventing EA was 0.30 μg/kg (95% CI: 0.21–1.00 μg/kg) ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 Further investigation into different bolus and maintenance infusion doses and rates needs to be conducted in procedural IVS. Rapid IV boluses of up to 1 mg/kg have been effective in reducing the incidence of emergence agitation at the end of general anesthesia in intubated children 31 ; this was seen with transient decreases in heart rate and MAP but was well tolerated in healthy children. This practice is not recommended in nonintubated patients or in adults who will not tolerate the rapid bolus.…”
Section: Discussionmentioning
confidence: 99%